Cardiovascular Manifestations of Covid-19 - Patrick Oyigebe Idoko; Velji Samuel Gomerep; Oladimeji Adebayo (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
COVID-19 enters the human cell via angiotensin Converting Enzyme 2 which is prevalent in the heart, lungs and blood vessels and as such, it’s cardinal manifestations are found in these organs. Cough and difficulty in breathing are the commonest cardiovascular manifestations of COVID-19. Other manifestations include chest pain, arrhythmias, thromboembolic events, heart failure, myocarditis and adult respiratory distress syndrome. Physicians have to be on the look out for these cardiovascular manifestations and address them, as COVID-19 patients with cardiovascular manifestations have a 5 fold higher mortality rate.